Perianth Phyllotaxis Is Polymorphic in the Basal Eudicot Anemone and Eranthis Species - Kitazawa, Miho S.; Fujimoto, Koichi (Frontiers in Ecology and Evolution, 2020)
Floral organs are clade-specifically arranged to either spiral or whorled (concentric circles) phyllotaxis. The basic number (merosity) of perianth organs within a whorl is limited to three in most monocots and to four or five in most eudicots. Although the Fibonacci number (3, 5) of merosity is well-known to agree with that of the spirals in phyllotaxis, the evolutionary relationship between whorls and spiral phyllotaxis remains unclear. Focusing on aestivation (the relative positioning of margins of flower organs in the bud) to capture phyllotaxis including merosity of whorled flowers, trimerous-whorled flowers and spiral ones coexist within populations with intraspecific variation in organ numbers. In addition, a recent mathematical model showed that tetramerous and pentamerous whorls developed from spiral organ initiation by incorporating a post-meristematic organ displacement, depending on the interaction among organ primordia. Therefore, integrating the variation of aestivation with the spiral-to-whorl development may elucidate the underlying mechanism of the continuous spiral-whorl relationship with the merosity diversification. Here, we showed that the aestivation of perianth organs (tepals) of mature flowers was intra-specifically variable but constrained in wild populations of several Anemone and Eranthis species (Ranunculaceae); the spiral arrangements coexisted within a small population, with dimerous, trimerous, tetramerous, and pentamerous double-whorled arrangements, despite considerable possibilities in the geometry. We determined mathematically that most of these constrained aestivations of 5 to 11-tepaled flowers emerge upon the spiral phyllotaxis with a divergence angle between subsequent organs of 90−102° or 135−144° (known as the Lucas and Fibonacci angles, respectively). Incorporating the post-meristematic organ displacement into the model, double-whorled arrangements work as templates to form multiple whorls, the merosity of which is stabilized to trimery, tetramery, or pentamery depending on the divergence angle. These results demonstrate that spiral phyllotaxis promotes the constrained coexistence of whorl and spiral rather than their interspecific dichotomy. This polymorphic phyllotaxis provides an evolutionary scenario in which the floral bauplans of angiosperms could be differentiated into tri-, tetra- and penta-radial symmetries.